Real-world evidence of survival benefit of remdesivir: study of 419 propensity score-matched patients hospitalized over the alpha and delta waves of COVID-19 in New Orleans, LA - Salvadori, Nicolas; Fridman, Moshe; Chiang, Mel; Chen, Linda; Wang, ChenYu; Lee, EunYoung; Fonseca, Vivian; Fusco, Dahlene N.; Jourdain, Gonzague; Drouin, Arnaud C. (Frontiers in Medicine, 2024)
Background: The direct acting antiviral remdesivir (RDV) has shown promising results in randomized clinical trials. This study is a unique report of real clinical practice RDV administration for COVID-19 from alpha through delta variant circulation in New Orleans, Louisiana (NOLA). Patients in NOLA have among US worst pre-COVID health outcomes, and the region was an early epicenter for severe COVID. Methods: Data were directly extracted from electronic medical records through REACHnet. Of 9106 adults with COVID, 1928 were admitted to inpatient care within 7 days of diagnosis. The propensity score is based upon 22 selected covariates, related to both RDV assignment and outcome of interest. RDV and non-RDV patients were matched 1:1 with replacement, by location and calendar period of admission. Primary and secondary endpoints were, death from any cause and inpatient discharge, within 28 and 14 days after inpatient admission. Results: Of 448 patients treated with RDV, 419 (94%) were successfully matched to a non-RDV patient. 145 (35%) patients received RDV for <5 days, 235 (56%) for 5 days, and 39 (9%) for >5 days. 96% of those on RDV received it within 2 days of admission. RDV was more frequently prescribed in patients with pneumonia (standardized difference: 0.75), respiratory failure, hypoxemia, or dependence on supplemental oxygen (0.69), and obesity (0.35) within 5 days prior to RDV initiation or corresponding day in non-RDV patients (index day). RDV patients were numerically more likely to be on steroids within 5 days prior to index day (86% vs 82%) and within 7 days after inpatient admission (96% vs 87%). RDV was significantly associated with lower risk of death within 14 days after admission (hazard ratio [HR]: 0.37, 95% CI: 0.19 to 0.69, p=0.002) but not within 28 days (HR: 0.62, 95% CI: 0.36 to 1.07, p=0.08). Discharge within 14 days of admission was significantly more likely for RDV patients (p<0.001) and numerically more likely within 28 days after admission (p=0.06). Conclusion: Overall, our findings support recommendation of RDV administration for COVID-19 in a highly comorbid, highly impoverished population representative of both Black and White subjects in the U.S. Gulf South.